The Best Employee Decision Support System Using the Analytical Hierarchy Process Method at PT ASDP Indonesia Ferry (Persero) - Deny Novianti; Anggi Oktaviani; Dahlia Sarkawi; Aldyanto Aldyanto; Ahmad Faren Syahidan (Jurnal Riset Informatika, 2023)
The selection of the best employees aims to spur employee morale in improving employee performance and dedication in the company. The selection of best employees is selected based on company criteria. PT ASDP Indonesia Ferry (PERSERO), the best employee criteria applied by the company are Work Quantity, Work Quality, Attendance, Teamwork, and Initiative. Employee assessment is carried out every month by the assessment team (Vice President (VP) and Manager). The problem faced is determining the best employees with criteria and alternatives that are calculated manually. This system is a Decision Support System (DSS) built using the Analytical Hierarchy Process (AHP) method. Previously, the evaluation process for selecting the best employees had never been done. Some of the problems encountered were the absence of an employee performance appraisal process, no appropriate selection method, and a Decision Support System (DSS) was not available that could make it easier to assess the selection of the best employees.